2018
DOI: 10.1093/annonc/mdy139
|View full text |Cite
|
Sign up to set email alerts
|

T cells isolated from patients with checkpoint inhibitor-resistant melanoma are functional and can mediate tumor regression

Abstract: Tumor-reactive T cells appear to heavily infiltrate the tumor microenvironment of patients who failed previous CPI treatment. These patients can still respond to an infusion of unselected autologous TILs. Our results warrant further testing of novel immune re-activation strategies in melanoma patients who failed multiple CPI therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 22 publications
0
66
0
2
Order By: Relevance
“…Although we conclude that IFN-γ should not be used concurrently with HD Cy or low-dose IL-2, IFN-γ may still play an important role in sensitizing SS for ACT. Interestingly, another recent ACT study showed the combination of interferon alpha and tumor-infiltrating lymphocyte (TIL) therapy, including Cy pretreatment in a similar dose, reinfusion of TILs, and postinfusion of IL-2 in a higher dose, was found to be safe in 12 patients in a published article by Andersen et al 26 However, future studies should avoid using IFN-γ during the immediate period around cell infusion and instead should consider alternative schedules, such as beginning IFN-γ weeks after cell infusion or at the time of progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although we conclude that IFN-γ should not be used concurrently with HD Cy or low-dose IL-2, IFN-γ may still play an important role in sensitizing SS for ACT. Interestingly, another recent ACT study showed the combination of interferon alpha and tumor-infiltrating lymphocyte (TIL) therapy, including Cy pretreatment in a similar dose, reinfusion of TILs, and postinfusion of IL-2 in a higher dose, was found to be safe in 12 patients in a published article by Andersen et al 26 However, future studies should avoid using IFN-γ during the immediate period around cell infusion and instead should consider alternative schedules, such as beginning IFN-γ weeks after cell infusion or at the time of progression.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were conducted in accordance with the Declaration of Helsinki and Good Clinical Practice. TILs were established in vitro with a two‐step process; the initial expansion to produce “young TILs” and the rapid expansion (REP) to produce REP TILs, as previously described in detail . Briefly, at day 0 tumor fragments were placed separately in the wells of a 24‐well/plate with 2 ml of standard complete TIL media (CM) consisting of RPMI‐1640 plus GlutaMAX and 25 mM HEPES (72400‐021, Gibco, Thermo Fisher Scientific, Waltham, MA) supplemented with 10% heat‐inactivated human AB serum (H4522‐100ML, Sigma‐Aldrich/Merck KGaA, Darmstadt, Germany), 100 U/ml penicillin and 100 μg/ml streptomycin (15140122, Gibco, Thermo Fisher Scientific, Waltham, MA), 1.25 μg/ml Fungizone® (Bristol‐Myers Squibb, New York, NY) and 6,000 IU/ml of rhIL‐2 (004184, Novartis, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…После чего отобранные изоляты TILs используют для получения конечного продукта для инфузии, что занимает еще две недели. В результате проведенных манипуляций получают суспензию клеток с концентрацией до 2•10 11 Т-лимфоцитов [12]. Однако существуют способы ускоренного получения TILs, при которых сокращают начальную фазу экспансии до двух недель и минуют стадию селекции, используя «неотобранные TILs» для получения конечного продукта.…”
Section: применение опухоль-инфильтрирующих лимфоцитов (Til-терапия)unclassified
“…Данные по эффективности применения TIL-терапии при лечении меланомы послужили основанием для продолжения исследований при других типах онкологических заболеваний внутренних органов, таких как рак яичников, рак груди, рак шейки матки, саркома и рак почки [8,12]. Однако в данном случае эффективность применения TILs оказалась невысокой.…”
Section: применение опухоль-инфильтрирующих лимфоцитов (Til-терапия)unclassified